Arthur Schopenhauer's Pessimistic Philosophy: 19th Century German Philosopher - Rido Putra; Endrika Widdia Putri; Rido Putra (Majalah Ilmu Pengetahuan dan Pemikiran Keagamaan Tajdid, 2023)
This article aims to explain the pessimistic philosophy of Arthur Schopenhauer—a 19th century German philosopher. The article is presented in a qualitative form using descriptive, interpretive and analytical methods. Schopenhaeur's philosophy of pessimism talks about world life as a place that gives birth to suffering. Suffering arises from the existence of desires. Will is a form of deficiency and the presence of want is suffering. As long as humans still have desires in their lives, humans will not be able to feel happiness. Human nature itself is a will, so achieving true happiness is something that is impossible for humans. However, man can rid himself of suffering by engaging in aesthetic contemplation and leading an ascetic life.